Student’s Conceptual Understanding in Physics Learning: A Systematic Literature Review - Pratiwi, Ficha Aulia Indah; Kuswanto, Heru; Ariswan, Ariswan (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
This article presents a systematic literature review (SLR) on concept understanding in physics learning. The method used in reviewing the literature is the SLR and PRISMA protocol with the stages of identification, screening, eligibility, inclusion, abstraction, and data analysis assisted using the Mendeley and VOSviewer applications. The findings of this study explain that there are still many difficulties, such as calculating in unsymmetrical field source distributions, such as two opposing point charges or currents, and misconceptions such as electricity and magnetism experienced by students and college students that affect students' understanding of concepts in physics learning. The challenges and misconceptions can be overcome by using various treatments, such as providing test instruments that can measure student understanding, developing conceptual models, and using virtual practicum activities. Future research needs to explore students' conceptual understanding of physics learning by using other topics that previous research has not studied.